Considering connections between Hollywood and biodiversity conservation. Issue 3 (10th January 2018) - Silk, Matthew J.; Crowley, Sarah L.; Woodhead, Anna J.; Nuno, Ana
Abstract: Cinema offers a substantial opportunity to share messages with a wide audience. However, there is little research or evidence about the potential benefits and risks of cinema for conservation. Given their global reach, cinematic representations could be important in raising awareness of conservation issues and species of concern, as well as encouraging greater audience engagement due to their heightened emotional impact on viewers. Yet there are also risks associated with increased exposure, including heightened visitor pressure to environmentally sensitive areas or changes to consumer demand for endangered species. Conservationists can better understand and engage with the film industry by studying the impact of movies on audience awareness and behavior, identifying measurable impacts on conservation outcomes, and engaging directly with the movie industry, for example, in an advisory capacity. This improved understanding and engagement can harness the industry's potential to enhance the positive impacts of movies featuring species, sites, and issues of conservation concern and to mitigate any negative effects. A robust evidence base for evaluating and planning these engagements, and for informing related policy and management decisions, needs to be built. Abstract : Article impact statement : Engaging with and understanding the impact of the movie industry could contribute to the success of biodiversity conservation. Abstract : La Consideración de las Conexiones entre Hollywood y la Conservación de la Biodiversidad Resumen: El cine ofrece una oportunidad sustancial para compartir mensajes con un público amplio. Sin embargo, hay pocas investigaciones o evidencias sobre los beneficios potenciales y los riesgos del cine para la conservación. Dado su alcance global, las representaciones cinematográficas podrían ser importantes para crear conciencia sobre los temas de conservación y las especies de importancia, así como alentar un mayor compromiso del público debido a su alto impacto emocional sobre los espectadores. Aunque también existen riesgos asociados con la exposición incrementada, incluyendo una mayor presión de visitantes a las áreas sensibles ambientalmente o cambios en la demanda de los consumidores por especies en peligro. Los conservacionistas pueden entender y comprometerse mejor con la industria del cine estudiando el impacto de las películas sobre la conciencia y comportamiento del público, identificando los impactos medibles sobre los resultados de la conservación, y colaborando directamente con la industria fílmica, por ejemplo, en una capacidad de asesor. Este entendimiento y compromiso mejorado puede aprovechar el potencial de la industria para aumentar los impactos positivos de las películas que incluyen especies, sitios y temas de importancia para la conservación y para mitigar cualquier efecto negativo. Se necesita construir una base sólida de evidencias para evaluar y planear estos compromisos y para informar las políticas relacionadas y las decisiones de manejo. 摘要: 好莱坞与生物多样性保护的联系 电影提供了许多与广大观众分享信息的机会。然而, 关于电影对于保护的潜在益处和风险的研究或证据却寥寥无几。考虑到电影在全球范围内的影响力及其对观众的情感强烈的影响力, 影像的呈现在帮助人们更好地认识保护问题和受关注的物种、鼓励更多的大众参与到保护中可以起到重要的作用。然而, 增加物种的曝光度也存在风险, 包括加重环境敏感地区的游客压力, 或改变消费者对濒危物种的需求。通过研究电影对观众意识和行为的影响, 可确定电影对保护效果可定量的影响, 并直接参与到电影行业中。例如, 担任电影顾问, 保护工作者可以更好地理解和参与电影行业。而更多的理解和参与将有助于充分发挥电影行业的潜力, 来提高以物种、地点和保护问题为特色的电影的积极作用, 同时减轻负面影响。最后, 还需要建立一个强有力的以证据为基础的方法来评估和规划对电影行业的参与, 并为相关政策和管理决定提供信息。【翻译 : 胡怡思 ; 审校 : 魏辅文】